IECON 2014 - 40th Annual Conference of the IEEE Industrial Electronics Society 2014
DOI: 10.1109/iecon.2014.7049290
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the supercapacitor-assisted surge absorber (SCASA) technique in a practical surge protector

Abstract: Their combination of large continuous energy ratings and very large time constants allows supercapacitors to be used in surge protection circuits. This fact, supported by recent research publications and laboratory tests, has assisted the authors to propose a new surge protection circuit topology known as the supercapacitor-assisted surge absorber (SCASA). This technique utilizes a multi-winding transformer, common surge protector devices such as metal oxide varistors (MOV) and/or semiconductor types combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Under this situation, energy dissipated in the SC loop is of importance, since it can create heat within the device (due to the effect of the ESR), and push the capacitor beyond its safe temp range. It can be shown that [12] energy dissipated in ESR of the SC as a ratio of energy absorbed by the SC is given by,…”
Section: Supercapacitors Capability To Absorb Transient Surgesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this situation, energy dissipated in the SC loop is of importance, since it can create heat within the device (due to the effect of the ESR), and push the capacitor beyond its safe temp range. It can be shown that [12] energy dissipated in ESR of the SC as a ratio of energy absorbed by the SC is given by,…”
Section: Supercapacitors Capability To Absorb Transient Surgesmentioning
confidence: 99%
“…Power electronics research group at the University of Waikato, launched a PhD thesis completed by the first author [10]- [14], based on the preliminary investigations which lead to the first patent [8]. As per detailed research published in [12]- [16], a uniquely new circuit topology as per Figure 10(d) was successfully developed by the team at Waikato. This was based on a step by step analysis of Figures 10(a) to 10(c).…”
Section: Supercapacitor Assisted Surge Absorber Conceptmentioning
confidence: 99%
“…This technique uses the advantage of a large time constant when a supercapacitor is connected to an RC circuit. Based on this concept, several SC assisted circuit topologies such as SC assisted light-emitting diodes (SCALED) [20], SC assisted low dropout regulator (SCALDO) [25] and SC assisted surge absorber (SCASA) [26] have already been developed. The fundamental background of this theory is summarized as follows.…”
Section: Supercapacitor Assisted Loss Circumvention Theorymentioning
confidence: 99%
“…Combining the above LCC with the case of a SC bank extending the time constant by several orders of magnitude, several SC-assisted (SCA) techniques have been developed at the University of Waikato [22]. Some examples are low drop-out regulator (SCALDO), temperature modification apparatus, high density inverter, surge absorber and LED lighting converter (supercapacitor-assisted LED (SCALED)) [8,[23][24][25].…”
Section: Rc Loop Fed By a DC Voltage Sourcementioning
confidence: 99%